2008
DOI: 10.1080/22201173.2008.10872552
|View full text |Cite
|
Sign up to set email alerts
|

Pain in osteoarthritis: A review of literature

Abstract: There is a vast body of evidence to suggest that osteoarthritis is a heterogenous condition that involves not only the articular cartilage but also an adaptive response of the bone and the synovium to a variety of environmental, genetic and biomechanical stresses. 5-11 There is also growing evidence pointing towards long term potentiation as the most likely mechanism for the transition of acute nociception to a chronic pain (CP) state. The complexity and plasticity of the nociceptive system not only serve surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Conventional wisdom argues that OA is a weight-bearing disease resulting in progressive and cumulative destruction of articular cartilage which leads to pain [17,20,22]. This progressive and destructive process consists of early cartilage fibrillation with developments to fissuring, ulceration, subchondral sclerosis, joint-space narrowing, and eventual full-thickness loss of hyaline cartilage [4,8,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional wisdom argues that OA is a weight-bearing disease resulting in progressive and cumulative destruction of articular cartilage which leads to pain [17,20,22]. This progressive and destructive process consists of early cartilage fibrillation with developments to fissuring, ulceration, subchondral sclerosis, joint-space narrowing, and eventual full-thickness loss of hyaline cartilage [4,8,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Although these treatments can be beneficial [10] in treating the symptoms of pain associated with the early stages of OA, the quality of these treatment modalities is largely unpredictable and can develop adverse side effects [19]. These treatments have been shown to be less effective during the late worsening stages of OA [20]. To date, there are no currently known treatments which block the progression of OA, nor the pain associated with this disease [21].…”
Section: Introductionmentioning
confidence: 99%
“…56,57) Another possible reason is that the rhMK promoted the retrieval of pathologic changed nervous system that was involved in the OA chronic pain. 2,3,5) Because beyond the bioactivity on cartilage, the neurotrophic and neurite outgrowth activities of MK have also been widely reported 22,23) . In addition, the study on Midkine knockout mice showed that the midkine (−/−) mice has a regenerative delay of the axonal damage after freezing injury of the sciatic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…2) More researches [2][3][4]35) indicate that OA occurrence and development is a long-term process with that the long-lasting knee injury or un-rational mechanical force induced dysfunction of the joint, which leading to the turn-over of the cartilage and bone and even the pathologic remodeling of vascular and peripheral nerve system of the joint, and this will further backward deteriorating the function of the joint over again. Once these pathological changes surpass a certain threshold, the OA is irreversible without any intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation